DEMOCRATIC SCHOOL MANAGEMENT AS AN ADMINISTRATIVE-PEDAGOGICAL PRACTICE IN BRAZIL - Pereira Paulino, Patrícia (Revista Gênero e Interdisciplinaridade, 2021)
This article aims to understand the factors that generate democratic school management in public elementary schools as an administrative-pedagogical practice in educational spaces in Brazil. Management in Brazilian public schools is a phenomenon that brings its peculiar characteristics, and involves multiple actors from school communities. The process takes into account the ability to manage daily practices, resolve conflicts, carry out negotiations, work with uncertainties and diverse interests that are present at all times in everyday school life. Therefore, it is essential to think of school management from the perspective not of something static or given a priori, but as a constant, dynamic and mainly democratic process, in which management is understood from the multiple interactions that are established between social actors in the environments schools and the occurrences experienced by them in the organizational daily life. Systematic observations were carried out based on observation at the Carlos Góis Municipal School, located in a place of high social vulnerability in the city of Belo Horizonte, Minas Gerais. The problems raised by this article point to a school management that is in constant process, dynamic, transitory and a product of constant conflicts and dialogues, interactions and experiences of different subjects in everyday school life in order to provide quality public education at school.